E-commerce Knowledge, Accounting Information Systems, Entrepreneurship science towards Entrepreneurial Interests ( Study of UNP Kediri Accounting Students ) - Aminah, Siti; Solikah, Mar'atus; Winarko, Sigit Puji (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research Objectives: The purpose of this research is to determine the influence of e-commerce knowledge accounting information systems entrepreneurship science on interest in entrepreneurship Research Method: This research uses quantitative research. The sampling technique uses a purposive sampling technique with sample calculation using the Slovin formula. The population in this study were students from the 2020 and 2021 Nusantara University PGRI Kediri Accounting Study Program. The sample obtained was 124 respondents. This research data uses SPSS version 27 analysis techniques Research Findings: The results of this research show that the influence of e-commerce knowledge, accounting information systems, and entrepreneurship science has a positive effect on interest in entrepreneurship Theoretical Contribution: It is hoped that this research can illustrate e-commerce knowledge and scientific development regarding accounting information systems, and entrepreneurship science and also serve as reference material for future researchers Practitioner Implications: It is hoped that this research can be used as evaluation material for e-commerce knowledge as well as material for consideration and input to provide outreach regarding entrepreneurship knowledge in the environment students Researcher Limitations: The limitations of this researcher are that the data source was obtained only from questionnaires from accounting study program students